Economic incentives for environmentally sustainable growth : Carbon pricing in OECD countries - Majanen, Pekka Mikael (My University, 2024)
The mitigation of greenhouse gas (GHG) emissions has become a common objective of environ-mental policies in many developed countries. The reason for this is the concern about the in-crease in the severity of damages caused by climate change which has been demonstrated in recent years. As the bulk of GHG emissions is made up of carbon dioxide (CO2) emissions, one of the economic tools to incentivize emissions mitigation is called carbon pricing. This policy sets a price for CO2 emissions which, in turn, encourages companies to abate emissions in an attempt to avoid additional costs. The two mechanisms which are used for carbon pricing are carbon tax and emissions trading system (ETS). While the mechanisms are different in how the price for emissions is set, they both aim to achieve the same goal of emissions mitigation. However, the actual effectiveness and other effects on the economy have been under scrutiny as no consensus on whether carbon pric-ing abates emissions and whether it undermines economic growth has not been found. This is because while the literature on the topics is extensive, the results are conflicting. Therefore, this study aims to find consensus by building on the discussion about carbon pricing in regard to the environment and economic growth. This study empirically analyzes the relationship between carbon pricing and CO2 emissions, and carbon pricing and economic growth in OECD countries between 1997 and 2021. The framework for the analysis is constructed based on the previous literature and is executed by regressing var-iables in a panel regression with fixed-effects -model. Moreover, the literature overview covers the most recent annual climate report by the OECD which provides evidence that there is a de-coupling between GHG emissions and economic growth. Lastly, the empirical analysis concludes with a brief causality analysis. The results support the claim that with current carbon prices and carbon price coverage, neither the carbon tax nor ETS are sufficient enough to significantly abate aggregate emissions. Howev-er, the study also finds that carbon pricing does not undermine economic growth. Moreover, the results provide evidence that implementing a carbon price via an ETS might even enhance eco-nomic growth. Therefore, the findings of this study suggest that the emissions-weighted carbon prices should be higher, either by increasing the price rate or decreasing the amount of price exemptions, to achieve aggregate CO2 emissions abatements. In addition, the more favorable carbon pricing mechanism seems to be implementing an ETS instead of carbon taxation.

Kasvihuonekaasupäästöjen vähentämisen tarve on noussut useiden kehittyneiden maiden yh-teiseksi ympäristöpolitiikan tavoitteeksi. Syynä tähän on ilmastonmuutoksesta johtuneet vakavat tuhot, jotka ovat korostuneet etenkin viime vuosina. Koska suurin osa kasvihuonekaasupäästöis-tä on hiilidioksidipäästöjä (CO2), eräs taloudellinen kannustin CO2-päästöjen vähentämiseksi on hiilihinnoittelu. Tämä kannustin asettaa hinnan CO2-päästöille, mikä kannustaa yrityksiä päästö-vähennyksiin kustannusleikkausten toivossa. Hiilihinnoittelua voidaan tehdä pääasiassa kahden eri mekanismin kautta: hiiliverotuksen ja pääs-tökaupan. Vaikka keinot määrittävät hinnan CO2-päästöille eri tavoin, molemmat niistä pyrkivät päästöjen vähennykseen. Hiilihinnoittelun todellinen vaikuttavuus päästövähennyksiin sekä ta-louden muihin osa-alueisiin on kuitenkin ollut kritiikin kohteena, sillä aikaisemmat tutkimukset eivät ole päässeet yksimielisyyteen siitä vähentääkö hiilihinnoittelu CO2-päästöjä ja onko sillä haittavaikutuksia talouskasvuun. Tämä yksimielisyyden puute johtuu siitä, että aihetta on tutkittu laajasti, mutta tulokset ovat ristiriitaisia. Tästä syystä tämä tutkimus pyrkii löytämään yksimieli-syyden jatkamalla keskustelua hiilihinnoittelun vaikutuksista ympäristöön ja talouteen. Tämä tutkimus analysoi empiirisesti hiilihinnoittelun ja CO2-päästöjen sekä hiilihinnoittelun ja talouskasvun keskinäisiä suhteita OECD-maissa vuosien 1997 ja 2021 välillä. Analyysin viitekehys rakentuu perustuen aikaisempaan kirjallisuuteen ja toteutetaan vakiovaikutteisella paneeliregres-siomallilla. Aikaisemmassa kirjallisuudessa huomioidaan myös viimeisin OECD:n vuosittainen il-mastoraportti, joka tarjoaa todisteita päästöjen ja taloudellisen kasvun erkaantumisesta. Empii-ristä regressioanalyysia tuetaan laatimalla kausaalinen analyysi. Tutkimuksen tulokset puoltavat väitettä, jonka mukaan hiiliveron sekä päästökaupan asettamat hiilihinnat ja niiden kattavuus eivät vähennä merkittävästi kokonaispäästöjä OECD maissa tutki-musperiodin aikana. Tulokset myös osoittavat, etteivät hiilihinnat kuitenkaan heikennä taloudel-lista kasvua. Tutkimus löysi todisteita siitä, että päästökaupalla asetetulla hiilihinnalla voi jopa olla positiivinen vaikutus talouskasvuun. Näin ollen tutkimuslöydökset osoittavat, että hiilihinto-jen tulisi olla korkeampia tai tiettyjen toimialojen hiilihinnoitteluvapauksia tulisi vähentää merkit-sevien päästövähennyksien saavuttamiseksi. Hiilihinnoittelumekanismeista päästökauppa näyt-täytyy hiiliveroa parempana vaihtoehto tutkimustuloksien mukaan, sillä päästökaupalla saattaa olla jopa talouskasvua edistäviä vaikutuksia.
Keywords: emissions; carbon dioxide; emission trade; greenhouse gases; climate changes; climate policy; environmental taxation; fi=Taloustiede|en=Economics|; fi=Taloustieteen maisteriohjelma|en=Master's Programme in Economics|